Determinan Tingkat Efisiensi Perbankan Syariah Di Indonesia: Two Stages Data Envelopment Analysis - Zulfikar Bagus Pambuko (Universitas Muhammadiyah Magelang, 2016)
Efficiency is an important indicator to observe the banks’ ability in resisting and facing the tight rivalry at banking industry. The study aims to evaluate the efficiency and to analyze the determinants of efficiency of Islamic bank in Indonesia on 2010 – 2013 with Two-Stage Data Envelopment Analysis approach. The objects of the study are 11 Islamic banks (BUS). The first phase of testing uses the Data Envelopment Analysis (DEA) method showed that the efficiency of Islamic bank is inefficient on managing the resources and small Islamic banks are more efficient than the larger. The second phase of testing uses Tobit model showed that Capital Adequacy Ratio (CAR), Return on Asset (ROA), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Net Interest Margin (NIM) have positive significant effect on the efficiency of Islamic banks, while Good Corporate Governance (GCG) has a negative significant effect. Moreover, the macroeconomic variables, such as GDP growth and inflation have no significant effect on efficiency of Islamic banks. It suggests that to realize the optimum level of Islamic banks’ efficiency is only related with bank-specific, while the volatility of macroeconomics condition contributes nothing